Electrode slurry, salt lake lithium extraction electrode and preparation method thereof
By using lithium-extracting electrode slurry with components such as electrode active substances and epoxy modified silicone resin, a salt lake lithium-extracting electrode with high efficiency, stability and environmental protection was prepared, which solved the performance of electrode materials during electrochemical lithium extraction. Problems of stability, low lithium extraction efficiency and poor environmental protection.
Patent Information
- Application Number
- CN202411352002.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-02-14
AI Technical Summary
During the process of electrochemical lithium extraction in Salt Lake, the electrode material performance is unstable, the lithium extraction efficiency is low, and the environmental protection is poor.
A lithium-extracting electrode slurry is used, including electrode active substances, epoxy modified silicone resins, conductive agents, chopped carbon fibers, pore-making agents and solvents, and a salt lake lithium-extracting electrode is prepared by a preparation method.
It improves the adsorption efficiency of lithium ions and the stability of the electrode, extends the service life of the electrode, and achieves an efficient and environmentally friendly lithium extraction in salt lakes.
Smart Images

Figure BDA0005062611720000061 
Figure BDA0005062611720000071 
Figure BDA0005062611720000081
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium extraction from salt lakes, and in particular to an electrode slurry, a lithium extraction electrode from a salt lake, and a preparation method thereof. Background Art
[0002] With the rapid development of the new energy industry, the demand for lithium has increased dramatically. As an important lithium salt product, lithium carbonate has been widely used in the field of new energy vehicles. At present, lithium carbonate mainly comes from lithium extraction from ores and lithium extraction from salt lakes. Among them, a large amount of reagents will be consumed in the process of lithium extraction from ores, and the cost of lithium extraction is relatively high; while the cost of lithium extraction from salt lakes is relatively low, and the lithium reserves in salt lake brine are huge, so lithium extraction from salt lakes has become the main direction of lithium salt production.
[0003] At present, the methods for extracting lithium from salt lakes mainly include solar evaporation, coprecipitation, solvent extraction, ion exchange adsorption and electrochemical lithium extraction technology; among them, solar evaporation relies on the natural evaporation process and is usually implemented in areas with sufficient sunshine and dry climate. It has the disadvantages of long cycle, great influence of seasons and climate, and large land area. The coprecipitation method is to add specific precipitants, such as carbonates or hydroxides, to the brine to form insoluble lithium compounds to precipitate impurities, which are then filtered and washed; but the above method requires a large amount of chemical reagents and may produce hazardous waste during the treatment process. The solvent extraction method is to mix an organic solvent with brine, transfer the lithium ions in the brine to the organic phase, and then recover the lithium through processes such as stripping or distillation. The disadvantages of the above method are complicated operation and high solvent cost. The ion exchange adsorption method uses an adsorbent with specific selectivity, such as ion exchange resin, to adsorb lithium ions from the brine; the adsorbent then recovers lithium through steps such as elution. The disadvantages of the above method are low efficiency in regeneration and reuse of the adsorbent and high long-term operating cost. Electrochemical lithium extraction is the process of extracting lithium from brine using electrochemical reactions. It has the advantages of simple operation and low cost, and is one of the most widely used methods. However, the adsorption efficiency, stability and environmental friendliness of electrode materials in electrochemical lithium extraction still need to be improved. Summary of the invention
[0004] In order to solve the problems of unstable electrode material performance, low lithium extraction efficiency and poor environmental protection in the process of electrochemical lithium extraction from salt lakes, the present application provides an electrode slurry, a salt lake lithium extraction electrode and a preparation method thereof.
[0005] In the first aspect, the present application provides a lithium extraction electrode slurry, which adopts the following technical solution: A lithium extraction electrode slurry comprises the following components in parts by weight: 95-105 parts of electrode active material, 40-60 parts of epoxy-modified silicone resin, 10-15 parts of conductive agent, 3-5 parts of short-cut carbon fiber, 10-20 parts of pore-forming agent and 65-80 parts of solvent.
[0006] The present application adopts electrode active materials, epoxy-modified silicone resins, conductive agents, etc. to prepare a lithium extraction electrode slurry. The salt lake lithium extraction electrode prepared using the above-mentioned lithium extraction electrode slurry has the advantages of high lithium extraction efficiency, good stability, long service life, and green environmental protection. It can meet the extraction of lithium-containing resources such as different salt lake brines and seawater, and provides important support for the realization of efficient and environmentally friendly salt lake lithium extraction.
[0007] In the lithium extraction electrode slurry of the present application, the epoxy-modified silicone resin is an adhesive with high porosity, high specific surface area and hydrophilic properties, and has good wettability. When it is added to the lithium extraction electrode slurry, the obtained salt lake lithium extraction electrode can wet the pores in a short time, shorten the mass transfer time of lithium ions, and thus improve the adsorption efficiency of lithium ions; in addition, the epoxy-modified silicone resin also has good wear resistance and pressure resistance, which can extend the service life of the electrode. The addition of chopped carbon fibers can, on the one hand, enable the materials in different areas of the coating layer to be interconnected in a bridging manner, which can reduce the degree of material shedding and serve the purpose of enhancing the structural strength of the electrode coating layer; on the other hand, it can also play a conductive role. The conductive agent can form an additional conductive network on the electrode surface, which helps the transfer of electrons between the electrode materials, thereby improving the extraction efficiency of lithium ions. The pore-forming agent can dissolve during the water washing process or decompose during the heating process to form large pores. These pores can increase the specific surface area of the electrode material, which is beneficial to the adsorption and diffusion of lithium ions. In addition, the above-mentioned pores can provide a stable structure to provide a buffer for the expansion and contraction of the electrode during the charge and discharge cycle, thereby improving the cycle stability of the electrode.
[0008] Optionally, the lithium extraction electrode slurry comprises the following components in parts by weight: 95-105 parts of electrode active material, 45-55 parts of epoxy-modified silicone resin, 10-15 parts of conductive agent, 3-5 parts of chopped carbon fiber, 10-20 parts of pore-forming agent and 65-80 parts of solvent.
[0009] In some embodiments, the weight parts of the epoxy-modified silicone resin may be 40-45 parts, 40-50 parts, 40-55 parts, 40-60 parts, 45-50 parts, 45-55 parts, 45-60 parts, 50-55 parts, 50-60 parts, or 55-60 parts.
[0010] In a specific embodiment, the weight proportion of the epoxy-modified silicone resin may also be 40 parts, 45 parts, 50 parts, 55 parts or 60 parts.
[0011] Optionally, the epoxy-modified silicone resin has a viscosity of 20-80S and an epoxy value of 0.02-0.16.
[0012] Optionally, the electrode active material is selected from LiFePO 4、LiMn 2 O 4 and LiNi x Co y Mn (1-x-y) O 2 One or more of; the LiNi x Co y Mn (1-x-y) O 2 Medium, 0 <x,y<1,0<x+y<1。
[0013] Optionally, the conductive agent is selected from one or more of nano carbon black, acetylene black, and superconductive carbon black, and the length of the chopped carbon fiber is 1-3 mm.
[0014] Optionally, the pore-forming agent is selected from NaCl, KCl, NaHCO 3 , KHCO 3 NH 4 ) 2 CO 3 and NH 4 HCO 3 One or more of; the solvent is selected from one or more of dimethyl carbonate, ethylene carbonate, diethyl carbonate, ethyl methyl carbonate and dipropyl carbonate.
[0015] In the present application, the green and environmentally friendly solvents such as the above-mentioned dimethyl carbonate are used to replace the traditional harmful solvent N-methylpyrrolidone, so as to reduce environmental pollution in the production process and reduce the adverse effects on human health.
[0016] In a second aspect, the present application provides a salt lake lithium extraction electrode, which is prepared using the lithium extraction electrode slurry and electrode.
[0017] The third invention, the present application provides a method for preparing a salt lake lithium extraction electrode.
[0018] A method for preparing a lithium extraction electrode from a salt lake comprises the following steps: preparing a lithium extraction electrode slurry, coating, and drying; coating: coating the lithium extraction electrode slurry evenly on the electrode, with a single-side coating thickness of 500-2000 μm; Drying: The coated electrode is first dried at 50-70°C for 1-5h, and then dried at 140-170°C for 1-2h to obtain a salt lake lithium extraction electrode.
[0019] In some embodiments, the single-side coating thickness may be 500-1000 μm, 500-1500 μm, 500-2000 μm, 1000-1500 μm, 1000-2000 μm, or 1500-2000 μm.
[0020] In a specific embodiment, the single-sided coating thickness may also be 500 μm, 1000 μm, 1500 μm or 2000 μm.
[0021] In some embodiments, the temperature of the second stage drying may be 140-160°C or 160-170°C.
[0022] In a specific embodiment, the temperature of the second drying stage can also be 140°C, 160°C or 170°C.
[0023] Optionally, the specific steps for preparing the lithium extraction electrode slurry are: first, mix the epoxy modified silicone resin with the solvent and stir for 5-10 minutes; then add the conductive agent, chopped carbon fiber, and pore-forming agent in sequence, and stir for 5-10 minutes after adding each component; finally, add the electrode active material, stir for 5-10 minutes, and then evacuate to -0.07 to -0.09MPa, stir rapidly to make the viscosity reach 40000-60000mPa.s, and obtain the lithium extraction electrode slurry.
[0024] In summary, this application has the following beneficial effects: 1. This application uses electrode active materials, epoxy-modified silicone resins, conductive agents, etc. to prepare a lithium extraction electrode slurry. The salt lake lithium extraction electrode prepared using the above lithium extraction electrode slurry has the advantages of high lithium extraction efficiency, good stability, long service life, and green environmental protection.
[0025] 2. The present application further controls the addition amount of epoxy-modified silicone resin in the lithium extraction electrode slurry within the range of 40-60 parts, which can achieve efficient extraction of lithium from salt lake brine.
[0026] 3. In the preparation method of the lithium extraction electrode from salt lake provided in the present application, the coating thickness of the lithium extraction electrode slurry is controlled in the range of 500-1500 μm, and the lithium extraction efficiency of the obtained lithium extraction electrode from salt lake is higher, and the lithium content in the brine can be reduced from 0.78 g / L to 0.12-0.13 g / L, and the adsorption capacity of Li on the under-lithium lithium iron phosphate electrode reaches 27.64-28.44 mg (Li) / g (LiFePO 4 ), the lithium content in the lithium-rich solution reaches 2.43-2.56g / L. DETAILED DESCRIPTION
[0027] In a first aspect, the present application provides a lithium extraction electrode slurry, comprising the following components in parts by weight: 95-105 parts of an electrode active material, 40-60 parts of an epoxy-modified silicone resin, 10-15 parts of a conductive agent, 3-5 parts of chopped carbon fibers, 10-20 parts of a pore-forming agent, and 65-80 parts of a solvent; further, the weight portion of the epoxy-modified silicone resin is 45-55 parts; Among them, the viscosity of the epoxy-modified silicone resin is 20-80S, and the epoxy value is 0.02-0.16; the electrode active material is selected from LiFePO 4 、LiMn 2 O 4 and LiNi x Co y Mn (1-x-y) O 2 One or more of them; in the LiNi x Co y Mn (1-x-y) O 2 , 0 < x, y < 1, 0 < x + y < 1; the conductive agent is selected from one or more of nano carbon black, acetylene black, and super conductive carbon black; the pore-forming agent is selected from NaCl, KCl, NaHCO 3 , KHCO 3 , (NH 4 ) 2 CO 3 and NH 4 HCO 3 One or more of them; the solvent is selected from one or more of dimethyl carbonate, ethylene carbonate, diethyl carbonate, methyl ethyl carbonate, and dipropyl carbonate; the length of the short carbon fiber is 1-3mm.
[0028] Second, this application provides a lithium extraction electrode from salt lakes, and its preparation method includes the following steps: (1) Prepare the lithium extraction electrode slurry: First, mix the epoxy-modified silicone resin with the solvent, stir for 5-10 minutes, the stirring frequency is 10-30Hz, and the dispersion frequency is 2000-3000Hz; then sequentially add the conductive agent, short carbon fiber, and pore-forming agent, and stir for 5-10 minutes after adding each component, the stirring frequency is 10-30Hz, and the dispersion frequency is 2000-3000Hz; finally, add the electrode active material, stir for 5-10 minutes, and then evacuate to -0.07~-0.09MPa, and stir rapidly, the stirring frequency is 10-40Hz, and the dispersion frequency is 2000-3000Hz to make the viscosity reach 40000-60000mPa.s to obtain the lithium extraction electrode slurry.
[0029] (2) Coating: Uniformly coat the lithium extraction electrode slurry on the electrode, and the single-sided coating thickness is 500-2000μm.
[0030] (3) Drying: First dry the coated electrode at 50-70°C for 1-5 hours, and then dry it at 140-170°C for 1-2 hours to obtain the lithium extraction electrode from salt lakes.
[0031] In the embodiments of the present application, the model of the epoxy-modified silicone resin is SH-023, the brand is 023-1 or 023-7, the viscosity of the epoxy-modified silicone resin with the brand 023-1 is 30-80S, and the epoxy value is 0.06-0.16, and the viscosity of the epoxy-modified silicone resin with the brand 023-7 is 20-60S, and the epoxy value is 0.02-0.07; the model of the superconductive carbon black is SUPER-P; the diameter of the chopped carbon fiber is 7μm, the length is 2mm, and the carbon content is 97%; the electrode is a titanium mesh with a thickness of 0.5mm and a specification of 20cm×24cm; the raw materials, reagents, solvents, etc. used in this application can all be obtained commercially.
[0032] The present application is further described in detail below in combination with preparation examples, embodiments and performance testing experiments.
[0033] Preparation Example 1-5 Preparation Examples 1-5 respectively provide a lithium extraction electrode slurry.
[0034] The difference between the above preparation examples is that the amount of epoxy-modified silicone resin added to the lithium extraction electrode slurry is shown in Table 1 below.
[0035] The preparation method of the lithium-extraction electrode slurry provided in Preparation Example 1-5 is as follows: first, epoxy-modified silicone resin (brand number 023-1) is mixed with 72g of dimethyl carbonate, stirred for 10min, stirring frequency is 20Hz, and dispersion frequency is 2500Hz; then, 13g of superconductive carbon black, 3g of chopped carbon fiber, 17g of NaHCO are added in sequence. 3 After adding each component, stir for 10 minutes, stirring frequency 20Hz, dispersion frequency 2500Hz; finally add 100g LiFePO 4 , stir for 10 minutes, then evacuate to -0.08MPa, stir rapidly, with a stirring frequency of 30Hz and a dispersion frequency of 2500Hz, so that the viscosity reaches 50000mPa.s to obtain a lithium extraction electrode slurry.
[0036] Table 1 Addition amount of epoxy-modified silicone resin in the lithium-extraction electrode slurry provided in Preparation Examples 1-5 Preparation Example Addition amount of epoxy modified silicone resin (g) 1 40 2 45 3 50 4 55 5 60 Preparation Example 6 Preparation Example 6 provides a lithium extraction electrode slurry.
[0037] The difference between the above preparation example and preparation example 3 is that: epoxy-modified silicone resin (brand number 023-7).
[0038] Comparative Preparation Example 1 Comparative Preparation Example 1 provides a lithium extraction electrode slurry.
[0039] The difference between the comparative preparation example and the preparation example 3 is that the addition amount of the epoxy-modified silicone resin (brand number 023-1) is 30 g.
[0040] Comparative Preparation Example 2 Comparative Preparation Example 2 provides a lithium extraction electrode slurry.
[0041] The difference between the comparative preparation example and the preparation example 3 is that the addition amount of the epoxy-modified silicone resin (brand number 023-1) is 70 g.
[0042] Comparative Preparation Example 3 Comparative Preparation Example 3 provides a lithium extraction electrode slurry.
[0043] The difference between the comparative preparation example and the preparation example 3 is that the epoxy-modified silicone resin (brand number 023-1) is replaced by silicone resin (Kramer, ZY1053).
[0044] Examples 1-6 Examples 1-6 each provide a salt lake lithium extraction electrode.
[0045] The difference between the above embodiments is that the lithium extraction electrode slurry used in the salt lake lithium extraction electrode is derived from Preparation Examples 1-6 respectively.
[0046] The method for preparing the lithium-extracting electrode from a salt lake of Examples 1-6 comprises the following steps: (1) Preparation of lithium-extracting electrode slurry: proceed according to Preparation Examples 1-6 respectively.
[0047] (2) Coating: The lithium extraction electrode slurry is evenly coated on the electrode, and the single-sided coating thickness is 1000 μm.
[0048] (3) Drying: The coated electrode was first dried at 70°C for 2 h and then dried at 160°C for 1 h to obtain a salt lake lithium extraction electrode.
[0049] Embodiment 7-9 Examples 7-9 each provide a salt lake lithium extraction electrode.
[0050] The difference between the above embodiment and embodiment 3 is that the single-sided coating thickness of the lithium extraction electrode slurry on the electrode is specifically shown in Table 2 below.
[0051] Table 2 Single-sided coating thickness of lithium-extraction electrode slurry on the electrode in Example 3, Example 7-9 Example Single-sided coating thickness (μm) 3 1000 7 500 8 1500 9 2000 Examples 10-17 Examples 10-17 each provide a salt lake lithium extraction electrode.
[0052] The difference between the above embodiment and embodiment 3 is: the drying temperature and time, which are specifically shown in Table 3 below.
[0053] Table 3 Temperature and time of drying in Example 3 and Examples 10-17 Comparative Examples 1-3 Comparative Examples 1-3 respectively provide a salt lake lithium extraction electrode.
[0054] The difference between the above embodiments is that the lithium extraction electrode slurry used in the salt lake lithium extraction electrode is derived from comparative preparation examples 1-3 respectively.
[0055] Comparative Example 4 Comparative Example 4 provides a salt lake lithium extraction electrode.
[0056] The difference between the comparative example and Example 3 is that the single-sided coating thickness of the lithium extraction electrode slurry on the electrode is 2300 μm.
[0057] Comparative Example 5 Comparative Example 5 provides a salt lake lithium extraction electrode.
[0058] The difference between the above comparative example and Example 13 is that the drying temperature in the second stage is 130°C.
[0059] Comparative Example 6 Comparative Example 6 provides a salt lake lithium extraction electrode.
[0060] The difference between the above comparative example and Example 13 is that the drying temperature in the second stage is 180°C.
[0061] Performance testing (1) Preparation of lithium-rich lithium iron phosphate electrode: A salt lake lithium extraction electrode (lithium-rich lithium iron phosphate electrode) was prepared according to the methods provided in Examples 1-17 and Comparative Examples 1-7.
[0062] (2) Preparation of under-lithiated lithium iron phosphate electrode: Prepare salt lake lithium extraction electrode according to the methods provided in Examples 1-17 and Comparative Examples 1-7, respectively. Then, use the salt lake lithium extraction electrode as the anode and the titanium mesh as the cathode in a KCl solution with a concentration of 10 g / L. Apply a voltage of 0.9 V to both ends of the electrode until the current density is lower than 0.5 A / m 2 , to obtain a lithium-deficient lithium iron phosphate electrode.
[0063] (3) Use an anion exchange membrane to separate the electrolytic cell into a delithiation chamber and a lithium insertion chamber, place the prepared lithium-rich lithium iron phosphate electrode (anode) in the delithiation chamber, and place the prepared lithium-deficient lithium iron phosphate electrode (cathode) in the lithium insertion chamber, inject 1L and 10g / L KCl solution as supporting electrolyte into the delithiation chamber, and inject 4L of brine to be treated into the lithium insertion chamber; apply 0.3V voltage to the anode and cathode respectively, and electrolyze for 6 hours at 15℃. Note: In the brine to be treated, the Li content is 0.78g / L, the Na content is 60g / L, and the Mg content is 9.5g / L.
[0064] (4) The lithium-rich lithium iron phosphate electrodes prepared in Examples 1-17 and Comparative Examples 1-7 and the corresponding lithium-deficient lithium iron phosphate electrodes were respectively used to carry out the lithium deintercalation test in the above step (3), and the lithium, sodium and magnesium concentrations in the brine, the lithium, sodium and magnesium concentrations in the lithium-rich solution (electrolyte) and the adsorption capacity of Li on the lithium-deficient lithium iron phosphate electrode were detected after the test. The results are shown in Table 4 below.
[0065] The concentrations of lithium, sodium and magnesium in brine and electrolyte were measured by atomic absorption spectrophotometer. The detection and calculation method of the adsorption capacity of Li on the under-lithiated lithium iron phosphate electrode is: Li adsorption capacity = (lithium concentration before brine treatment × volume - lithium concentration after brine treatment × volume) / (LiFePO on the electrode plate 4 Total Table 4 Performance test results of the salt lake lithium extraction electrodes prepared in Examples 1-17 and Comparative Examples 1-7 According to the test results in Table 3, the salt lake lithium extraction electrode provided by Examples 1-17 has a good interception effect on impurity ions such as sodium and magnesium, and exhibits good lithium selectivity.
[0066] The test results of Examples 1-6 and Comparative Examples 1-3 show that the lithium content in the brine can be reduced to 0.12-0.17 g / L by using the salt lake lithium extraction electrode provided in Examples 1-5, and the adsorption capacity of Li on the under-lithium lithium iron phosphate electrode is 25.41-28.44 mg (Li) / g (LiFePO 4 ), the lithium content in the lithium-rich solution is 2.17-2.56 g / L; while the lithium content in the brine is only reduced to 0.20-25 g / L by using the salt lake lithium extraction electrode provided in Comparative Examples 1-3, and the adsorption capacity of Li on the lithium-poor lithium iron phosphate electrode is 21.98-23.47 mg (Li) / g (LiFePO 4), the lithium content in the lithium-rich solution is 1.79-1.93 g / L. Therefore, it is shown that the application uses epoxy-modified silicone resin as a binder for lithium-extracting electrode slurry, and controls its addition amount within the range of 40-60 parts, which can achieve efficient extraction of lithium from salt lake brine.
[0067] It can be seen from the test results of Example 3, Examples 7-9, and Comparative Example 4 that with the increase in the coating thickness of the lithium extraction electrode slurry during the preparation of the salt lake lithium extraction electrode, after the lithium deintercalation test, the lithium content in the brine first decreases and then increases, and the lithium content in the lithium-rich solution and the adsorption capacity of Li on the lithium-deficient lithium iron phosphate electrode both show a trend of first increasing and then decreasing; further comparison shows that the use of the salt lake lithium extraction electrodes of Examples 3 and Examples 7-8 for lithium extraction from brine can reduce the lithium content in the brine to 0.12-0.13 g / L, and the adsorption capacity of Li on the lithium-deficient lithium iron phosphate electrode reaches 27.64-28.44 mg (Li) / g (LiFePO 4 ), the lithium content in the lithium-rich solution reaches 2.43-2.56 g / L. Therefore, it is explained that the present application further controls the coating thickness of the lithium-extraction electrode slurry in the process of preparing the salt lake lithium-extraction electrode within the range of 500-1500 μm, and the lithium-extraction efficiency of the obtained salt lake lithium-extraction electrode is higher.
[0068] The test results of Example 3, Examples 10-17, and Comparative Examples 5-6 show that the lithium content in the brine can be reduced to 0.10-0.14 g / L by using the salt lake lithium extraction electrodes of Examples 3 and Examples 10-17, and the adsorption capacity of Li on the under-lithium lithium iron phosphate electrode is 28.17-28.47 mg (Li) / g (LiFePO 4 ), the lithium content in the lithium-rich solution is 2.39-2.56 g / L; while the lithium extraction electrode of the salt lake in Comparative Examples 5-6 is used to extract lithium from brine, the lithium content in the brine can be reduced to only 0.22-0.26 g / L, and the adsorption capacity of Li on the lithium-deficient lithium iron phosphate electrode is only 22.51-23.68 mg (Li) / g (LiFePO 4 ), the lithium content in the lithium-rich solution is 1.66-1.97 g / L. Therefore, it is shown that the present application adopts a two-step drying process and controls the temperature of the second step within the range of 140-170°C, which can achieve efficient extraction of lithium from salt lake brine.
[0069] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. A lithium extraction electrode slurry, characterized in that: The invention comprises the following components in parts by weight: 95-105 parts of electrode active material, 40-60 parts of epoxy-modified organic silicon resin, 10-15 parts of conductive agent, 3-5 parts of short-cut carbon fiber, 10-20 parts of pore-forming agent and 65-80 parts of solvent.
2. The lithium extraction electrode slurry according to claim 1, characterized in that: The invention comprises the following components in parts by weight: 95-105 parts of electrode active material, 45-55 parts of epoxy-modified organic silicon resin, 10-15 parts of conductive agent, 3-5 parts of short-cut carbon fiber, 10-20 parts of pore-forming agent and 65-80 parts of solvent.
3. The lithium extraction electrode slurry according to claim 1, characterized in that: The epoxy-modified silicone resin has a viscosity of 20-80S and an epoxy value of 0.02-0.
16.
4. The lithium extraction electrode slurry according to claim 1, characterized in that: The electrode active material is selected from LiFePO4, LiMn2O4 and LiNi x Co y Mn (1-x-y) One or more of O2; The LiNi x Co y Mn (1-x-y) O2, 0 <x,y<1, 0<x+y<1。 5. The lithium extraction electrode slurry according to claim 1, characterized in that: The conductive agent is selected from one or more of nano carbon black, acetylene black, and superconductive carbon black, and the length of the chopped carbon fiber is 1-3 mm.
6. The lithium extraction electrode slurry according to claim 1, characterized in that: The pore-forming agent is selected from one or more of NaCl, KCl, NaHCO3, KHCO3, (NH4)2CO3 and NH4HCO3; the solvent is selected from one or more of dimethyl carbonate, ethylene carbonate, diethyl carbonate, ethyl methyl carbonate and dipropyl carbonate.
7. A salt lake lithium extraction electrode, characterized in that: The lithium-extracting electrode slurry and electrode are prepared using any one of claims 1 to 6.
8. The method for preparing a lithium-extracting electrode from a salt lake according to claim 7, characterized in that: The following steps are involved: Preparation of lithium-extraction electrode slurry, coating, and drying; Coating: The lithium extraction electrode slurry is evenly coated on the electrode, with a single-sided coating thickness of 500-2000μm; Drying: The coated electrode is first dried at 50-70°C for 1-5h, and then dried at 140-170°C for 1-2h to obtain a salt lake lithium extraction electrode.
9. The method for preparing a lithium-extracting electrode from a salt lake according to claim 8, characterized in that: The specific steps for preparing lithium extraction electrode slurry are: First, the epoxy-modified silicone resin is mixed with the solvent and stirred for 5-10 minutes; then the conductive agent, chopped carbon fiber and pore-forming agent are added in sequence, and each component is stirred for 5-10 minutes; finally, the electrode active material is added, stirred for 5-10 minutes, and then vacuumed to -0.07~-0.09MPa, and stirred rapidly to make the viscosity reach 40000-60000mPa.s to obtain the lithium extraction electrode slurry.